2001
DOI: 10.1128/jvi.75.20.9819-9827.2001
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus Protein p54 Interacts with the Microtubular Motor Complex through Direct Binding to Light-Chain Dynein

Abstract: Dynein is a minus-end-directed microtubule-associated motor protein involved in cargo transport in the cytoplasm. African swine fever virus (ASFV), a large DNA virus, hijacks the microtubule motor complex cellular transport machinery during virus infection of the cell through direct binding of virus protein p54 to the light chain of cytoplasmic dynein (LC8). Interaction of p54 and LC8 occurs both in vitro and in cells, and the two proteins colocalize at the microtubular organizing center during viral infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
179
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 62 publications
4
179
0
3
Order By: Relevance
“…Higher apparent affinity of DYNLL binding to dimeric protein fragments was first noted by studying DYNLL2 and myoVa interactions (2) and later attributed to avidity (15). This hypothesis questioned the original proposal of heterodimeric cargo adapter role of DYNLL on dynein and myoVa motor complexes (6,7,21,(55)(56)(57)(58).…”
Section: Fine-tuning Of Affinities Is Achieved Through Diversity Of Bmentioning
confidence: 85%
“…Higher apparent affinity of DYNLL binding to dimeric protein fragments was first noted by studying DYNLL2 and myoVa interactions (2) and later attributed to avidity (15). This hypothesis questioned the original proposal of heterodimeric cargo adapter role of DYNLL on dynein and myoVa motor complexes (6,7,21,(55)(56)(57)(58).…”
Section: Fine-tuning Of Affinities Is Achieved Through Diversity Of Bmentioning
confidence: 85%
“…Although in our complex the corresponding T157 is still spatially close to F73, the pi-cation interaction is no longer possible and polar interactions involve the side chains of N10 and H68. Importantly, mutational analyses showed that binding activity was maintained in mutants preserving the T-SQT motif indicating that T157 is essential for binding [12]. Remarkably, a threonine is also present in the nNOS peptide in the equivalent position.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sequences responsible for p53, PTHrP, and Rb interaction with MTs/dynein remain largely undefined, short sequences from several other proteins have been identified, using the yeast two-hybrid system and proteomics approaches, which confer interaction with the dynein light chains (DLC), LC8 and Tctex-1. These sequences variously include the consensus motifs KSTQT (single letter amino acid code) and GIQVD for LC8, as well as less well-defined motifs for Tctex-1 interaction, including SKCSR (Raux et al, 2000;Alonso et al, 2001;Poisson et al, 2001;RodriguezCrespo et al, 2001;Mueller et al, 2002;Martinez-Moreno et al, 2003;Sugai et al, 2003;Lo et al, 2005). DLC-ASs have been suggested to mediate cargo association with dynein motor complexes to effect nuclear targeting, so that they could potentially be exploited for delivery of therapeutics to This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E07-01-0030) on June 13, 2007. cell nuclei (Cohen et al, 2005;Mastrobattista et al, 2006a,b); however, this has never been directly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, it has been reported that DLC association can sequester proteins in the cytoplasm, inhibiting nuclear entry of protein (Ninomiya et al, 2005) or localization at the nuclear membrane (Bouillet and Strasser, 2002). Given the requirement for viral trafficking to the nucleus/perinuclear MTOC and the presence of LC8 binding DLC-ASs in numerous viral proteins, it has been conjectured that LC8 DLC-AS-containing proteins could direct viral particles to this site, although direct evidence for this is lacking (Alonso et al, 2001;Rodriguez-Crespo et al, 2001;Dohner et al, 2005;Greber and Way, 2006). We set out to examine nuclear localization of the rabies virus phosphoprotein (P-protein [RPP]) in live cells.…”
mentioning
confidence: 99%